Estimation of pH effect on the structure and stability of kinase domain of human integrin-linked kinase. Issue 1 (2nd January 2019) - Syed, Sunayana Begum; Shahbaaz, Mohd; Khan, Sabab Hassan; Srivastava, Saurabha; Islam, Asimul; Ahmad, Faizan; Hassan, Md. Imtaiyaz
Abstract : Integrin-linked kinase (ILK) is an evolutionarily conserved Ser/Thr protein kinase, involved in many physiological functions such as signal transduction, actin rearrangement, cell proliferation, migration, polarisation, angiogenesis and apoptosis. An increased expression of ILK is associated with different cancers and thus considered as an attractive target for cancer therapy. We have successfully cloned, expressed and purified the kinase domain (193–446 residues) of ILK. To see the effect of pH on the structure and conformation, we performed circular diachroism, fluorescence and absorbance measurements in a wide range of pH conditions. We observed that within the range of pH 7.5–11.0, ILK193–446 maintains its both secondary and tertiary structures. While visible aggregates were observed under the acidic pH 2.0–5.5 conditions, in order to complement these observations, we have performed molecular dynamics simulations of this kinase domain by mimicking diverse pH conditions which enabled us to see conformational preferences of the protein under such conditions. A significant correlation between the spectroscopic and molecular dynamics simulation was observed. These findings are useful to understand the conformation of ILK protein under certain pH condition which may be further implicated in the drug design and discovery.